2019
DOI: 10.1016/j.rbmo.2019.06.007
|View full text |Cite
|
Sign up to set email alerts
|

A propensity-matched study of the association between pre-pregnancy maternal underweight and perinatal outcomes of singletons conceived through assisted reproductive technology

Abstract: A propensity-matched study of the association between prepregnancy maternal underweight and perinatal outcomes among singletons based on an ART cohort,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 45 publications
0
8
0
Order By: Relevance
“…Furthermore, we investigated the impact of pre-pregnancy maternal underweight on birth outcomes among ART-conceived singletons in a previous retrospective cohort. An interaction was found between maternal underweight and timing of embryo transfer (fresh/frozen embryo transfer) on gestational age (underweight vs. normal weight: fresh: difference = −0.07 week, 95% CI: −0.22 to 0.09 week; frozen: difference = 0.15 week, 95% CI: −0.05 to 0.36 week; P for interactio n = 0.038) ( 25 ). In our study, we found a significant interaction between pre-pregnancy maternal BMI and timing of embryo transfer (fresh/frozen embryo transfer) on PTB and LGA in ART-conceived singletons.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, we investigated the impact of pre-pregnancy maternal underweight on birth outcomes among ART-conceived singletons in a previous retrospective cohort. An interaction was found between maternal underweight and timing of embryo transfer (fresh/frozen embryo transfer) on gestational age (underweight vs. normal weight: fresh: difference = −0.07 week, 95% CI: −0.22 to 0.09 week; frozen: difference = 0.15 week, 95% CI: −0.05 to 0.36 week; P for interactio n = 0.038) ( 25 ). In our study, we found a significant interaction between pre-pregnancy maternal BMI and timing of embryo transfer (fresh/frozen embryo transfer) on PTB and LGA in ART-conceived singletons.…”
Section: Discussionmentioning
confidence: 99%
“…Based on the literature (24,25), we collected all potential correlated factors of perinatal outcomes from the records. These include the year of embryo transfer (2006-2009, 2010-2012, or 2013-2015), maternal age, gravidity (0, 1-2, or, ≥3), parity (0 or ≥1), main etiology of infertility (tubal factor, ovarian factor, male factor, or other reasons), sperm donation (yes or no), fertilization method (ICSI, IVF, or IVF + ICSI), fresh/frozen embryo transfer, blastocyst/cleavage-stage transfer, assisted hatching (yes or no), antral follicle count, basal serum follicle-stimulating hormone (FSH) level, endometrial thickness, maternal smoking history (yes or no), and gestational weight gain.…”
Section: Confounding Variablesmentioning
confidence: 99%
“…Moreover, epidemiological studies have been suggested that maternal overweight and obesity have been shown to be association with PTB (Lynch et al 2014;Shaw et al 2014;Su et al 2020), LBW (Rahman et al 2015) and adverse maternal health Manuscript to be reviewed outcomes, such as gestational hypertension (Santos et al 2019) and cesarean delivery (Paidas Teefey et al 2020;Rahman et al 2015). Similarly, several observational studies show that underweight women in pre-pregnancy is the major risk factor for LBW and PTB (Ehrenberg et al 2003;Madzia et al 2020;Qu et al 2019). However, the conclusions of various studies on the correlation between pre-pregnancy BMI and PTB appear to be paradoxical.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, epidemiological studies have been suggested that maternal overweight and obesity have been shown to be association with PTB (Lynch et al, 2014;Shaw et al, 2014;Su et al, 2020), LBW (Rahman et al, 2015) and adverse maternal health outcomes, such as gestational hypertension (Santos et al, 2019) and cesarean delivery (PaidasTeefey et al, 2020;Rahman et al, 2015). Similarly, several observational studies show that underweight women in pre-pregnancy is the major risk factor for LBW and PTB (Ehrenberg et al, 2003;Madzia et al, 2020;Qu et al, 2019). However, the conclusions of various studies on the correlation between pre-pregnancy BMI and PTB appear to be paradoxical.…”
Section: Introductionmentioning
confidence: 99%